Total and Inorganic Arsenic Concentrations in Different Species of Economically Important Algae Harvested from Coastal Zones of Chile - Diaz-Schulze, O (2012)
Chile is one of the major producers of phytocolloids extracted from seaweed. Multicellular algae are considered to be primary accumulators of arsenic. We analyzed 14 species of algae belonging to the groups Rhodophyceae (10), Phaeophyceae (3) and Chlorophyceae (1) from different coastal zones of Chile in 2003-2004. Dry ashing mineralization (for total As) and acid digestion (for inorganic As) together with quantification by flow injection hydride generation atomic absorption spectrometry (FI-HG-AAS) were employed. In general, total arsenic concentrations varied between 3.0 and 68mgkg -1, whereas inorganic arsenic concentrations ranged between 0.15 and 1.06mgkg -1. The algal species Durvillaea antarctica and Porphyra columbina, used for direct human consumption, did not have inorganic arsenic levels that represent a health risk to consumers. Among species used for phytocolloids production, such as Macrocystis piryfera, Gracilaria chilensis and Gigartina skottsbergii, observed levels of inorganic arsenic were greater than 1mgkg -1, the limit value established by the regulations of some countries. Among the 14 species of algae tested, inorganic arsenic levels were between 0.8% and 13% of the total arsenic concentrations; that is, arsenic present in these algae was found primarily as organic arsenic. © 2011 Elsevier Ltd.